2007
DOI: 10.1093/bja/aem069
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose remifentanil to suppress haemodynamic responses to noxious stimuli in cardiac surgery: a dose-finding study

Abstract: Remifentanil at 0.3 and 0.4 microg kg-1 min-1 in combination with a target-controlled propofol infusion in the pre-bypass period is well tolerated. It appears to mitigate potentially hazardous haemodynamic responses from stressful stimuli equally well as higher doses when compared with data from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The finding that remifentanil was found to reduce the duration of mechanical ventilation, time to extubation after sedation cessation, and ICU-LOS may be highly related to the unique pharmacokinetics and pharmacodynamics of remifentanil, namely, its rapid onset and offset, context-sensitive half-life that is hardly affected by the duration of infusion, and elimination that is independent of liver or renal function [ 14 , 15 ]. In the subgroups, the results of the studies comparing remifentanil with fentanyl showed a maximal mean difference of 3.85 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that remifentanil was found to reduce the duration of mechanical ventilation, time to extubation after sedation cessation, and ICU-LOS may be highly related to the unique pharmacokinetics and pharmacodynamics of remifentanil, namely, its rapid onset and offset, context-sensitive half-life that is hardly affected by the duration of infusion, and elimination that is independent of liver or renal function [ 14 , 15 ]. In the subgroups, the results of the studies comparing remifentanil with fentanyl showed a maximal mean difference of 3.85 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil may lead to reduced cardiac output and hypotension. 23 It has also been suggested that sensitivity of peripheral alpha-adrenergic receptors is decreased in schizophrenic patients treated with antipsychotic agents such as haloperidol or chlorpromazine, 24 and that epinephrine 25 contained in lidocaine used as a local anaesthetic agent causes dilation of peripheral blood vessels. Anaesthesia for ordinary dental procedures might be excessively deep.…”
Section: Discussionmentioning
confidence: 99%
“…Both these techniques provide excellent intra operative analgesia. Remifentanil infusion has the added advantage of reducing stress response to sternotomy (50), rapid titrability, a favorable context sensitive half time (51) allowing for rapid recovery, reducing coughing (52,53) and bucking on extubation.…”
Section: Induction and Maintenance Of Anaesthesiamentioning
confidence: 99%